Bleeding Time and False Aneurysm Incidence on Cattle Slaughtering Using Non-Penetrative Pre-Slaughter Stunning in Indonesia - Supratikno; H. Setijanto; H. Nuraini; S. Agungpriyono (Faculty of Animal Science, Bogor Agricultural University, 2022)
The use of non-penetrating pre-slaughter stunning (NPPSS) in ruminants remains a contentious issue in Indonesia since it is thought to interfere with the bleeding. This paper evaluated the bleeding time (BT), incidence of the false aneurysm (FA), and factors influencing these parameters in 460 NPPSS and 50 non-NPPSS slaughters in Indonesia. In this research, bodyweight, neck skin fold, sex, incisors condition, stunner strength, door closed-final stunning interval, number of shots, stunning success rate (SSR), stunning final-slaughter interval, broken skull, shooting placement, stunner-men and slaughter-men competencies, incision direction, incision location, BT, and FA were assessed for NPPSS slaughter. The same parameters were also assessed for non-NPPSS except the stunning parameter. The results showed that the BT of the non-NPPSS slaughters (187±47.37 seconds) was faster than that of the NPPSS slaughters, with the BT for the NPPSS dependent upon the level of unconsciousness. The longest BT was found in fully unconscious cattle shot once (304.32±69.76 seconds). The risk of FA incidence in non-NPPSS cattle was higher than in the NPPSS cattle. The FA incidence was 2.64 times higher in non-NPPSS cattle than in unconscious NPPSS cattle. The BT of non-NPPSS cattle was affected by FA, whereas the NPPSS cattle were affected by SSR, number of shots, broken skull, and FA incidence. The primary influence factor of FA in non-NPPSS cattle was incision location, whereas the NPPSS cattle were DCFS, incision location, and incision direction. Based on the results of this study, it can be concluded that the use of NPPSS prolongs BT and reduces the risk of FA in the slaughter of Australian Brahman cross cattle.